1943
DOI: 10.1021/ie50400a016
|View full text |Cite
|
Sign up to set email alerts
|

Isopropyl Alcohol–Water System: Density-Composition Data and Pycnometric Technique

Abstract: The density of pure anhydrous isopropyl alcohol, prepared by treatment with calcium oxide and subsequent fractionation until the still liquid and distillate were identical, was found to be 0.77223 ± 0.00002 gram per ml. at 35°G. Density-composition data were obtained for the system isopropyl alcohol-water at FOR determining accurately and rapidly the composition of small alcohol-water samples, an improved pycnometric technique has been developed using 6-8 ml.pycnometer bulbs of the Ostwald type, fitted with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

1952
1952
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“… 28 For small boxes without protein, we compared our simulations of IPA OPLS +H 2 O to experiments by Langdon and Keyes that determined the density for IPA+H 2 O systems at different temperatures. 36 We found that our mixed box of IPA OPLS +H 2 O reproduced the experimental density at 308 K (0.830g/mL) to within 0.06%. Our ability to replicate this fundamental data confirmed the use of good parameters for our IPA+H 2 O systems.…”
Section: Results and Discussionsupporting
confidence: 59%
“… 28 For small boxes without protein, we compared our simulations of IPA OPLS +H 2 O to experiments by Langdon and Keyes that determined the density for IPA+H 2 O systems at different temperatures. 36 We found that our mixed box of IPA OPLS +H 2 O reproduced the experimental density at 308 K (0.830g/mL) to within 0.06%. Our ability to replicate this fundamental data confirmed the use of good parameters for our IPA+H 2 O systems.…”
Section: Results and Discussionsupporting
confidence: 59%
“…На эффективность тарелки может оказывать влияние множество факторов, включая конструктивные факторы ( тип и размеры тарелки, размер отверстий, высота переливной стенки), рабочие условия ( скорости жидкости и пара) и характеристики смеси на тарелке. Факторы, которые получили внимание у исследователей [19][20][21], включали в себя: высоту переливной перегородки, размер отверстий на тарелке, смешивание жидкости, унос жидкости, режимы течения потоков, флегмовое число, состав и поверхностное натяжение компонентов смеси.…”
Section: факторы влияющие на эффективностьunclassified
“…Лэнгдона и Д.Б. Кииса [19], изучали влияние концентрации на эффективность тарелок различных типов и конфигураций колонны. Исследование У.М.…”
Section: размер отверстий на тарелке и высота переливной перегородкиunclassified
See 2 more Smart Citations